Genome-Wide Gene Expressions Respond Differently to A-subgenome Origins in Brassica napus Synthetic Hybrids and Natural Allotetraploid - Zhang, Dawei; Pan, Qi; Tan, Chen; Zhu, Bin; Ge, Xianhong; Shao, Yujiao; Li, Zaiyun (Frontiers in Plant Science, 2016)
The young allotetraploid Brassica napus (2n=38, AACC) is one of models to study the genomic responses to allopolyploidization. The extraction of AA component from natural B. napus should provide a unique opportunity to reveal the genome interplay for gene expressions during the evolution. Herein, B. napus hybrids (2n=19, AC) between the extracted and extant B. rapa (2n=20, AA) and the same B. oleracea genotype (2n=18, CC) were studied by RNA-seq and compared with natural B. napus donor, to reveal the gene expression changes from hybridization and domestication and the effects of A genome with different origins. Upon the initial merger of two diploid genomes, additive gene expression was prevalent in these two hybrids, for nonadditively expressed genes only represented a small portion of total expressed genes. A high proportion of genes exhibited expression level dominance, with no preference to either of the parental genomes. Comparison of homoeolog expressions also showed no bias toward any genomes and the parental expression patterns were often maintained in the hybrids and natural allotetraploids. Although the overall patterns of gene expression were highly conserved between two hybrids, the extracted B. rapa responded less and appeared more compatible for hybridization than the extant B. rapa. Our results suggested that expression level dominance and homoeolog expressions bias were balanced at the initial stage of genome merger, and such balance were largely maintained during the domestication of B. napus, despite the increased extent over time.